Personality traits and knowledge sharing behavior of software engineers - Rehman, M. (Institute of Electrical and Electronics Engineers Inc., 2017)
Unfortunately, the work so far has focused on the technical aspects of Software Engineering rather than non-technical aspects. This has led to the conclusion that Software Engineering is still an immature profession in terms of research. There is still room to do more research in this profession. Besides, this field has also become broad in nature and covers many aspects which are from other domains like personality and knowledge sharing behavior (behavioral outcome). Personality and knowledge sharing behavior are very important components for Software Engineering and that is why recently there is an increase in research papers on these aspects of Software Engineers. This paper also analyzed the personality traits of Software Engineers and the relationship between personality traits and knowledge sharing behavior. Big Five Personality Traits were used to analyze the personality of Software Engineers. Questionnaire method was used to collect response from Malaysian Software Engineers. Results indicated that Software Engineers scored high on extraversion and conscientiousness personality traits whereas they were moderate on openness to experience and agreeableness. Results also indicated positive relationship with knowledge sharing behavior between all personality traits except neuroticism which showed negative relationship. © 2017 IEEE.